Phonetic improvement with an obturator of the acquired defect in a case of Palatal Mucoepidermoid Carcinoma: a case report / Aiemeeza Rajali, Yusnidar Tajul Arifin and Nik Rahayyu Nik Zulkifeli - Rajali, Aiemeeza; Tajul Arifin, Yusnidar; Nik Zulkifeli, Nik Rahayyu (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Introduction: Following surgical resection of palatal mucoepidermoid carcinoma (MEC), the resulting defect is best corrected with surgical reconstruction and rehabilitation. However, the patient's clinical course with ill-defined recurrence resulted in the fabrication of cobalt chromium obturator prosthesis as the best treatment option for reliable restoration. Case description: A 48 years old Chinese man was referred for construction of an obturator prosthesis after one year following a wide excision surgery for low grade mucoepidermoid carcinoma of the hard palate. Leaving him with a maxillary defect of Okay Class 1a classification with oronasal communication. He complained of difficulty in speaking, inability to properly chew food and fluid leakage into his nose due to looseness of the previous surgical obturator. An obturator with a cobalt chromium framework was fabricated and silicone material for direct relining is used to provide cushioning and path of insertion to the obturator. Discussion: The defect created post surgically had caused several problems such as deglutition and feeding difficulties and changing of the sounds of speech. Such a properly designed obturator prosthesis obtained its retention, support and stability from remaining teeth. Not only it distributed force equally to the remaining teeth and provided cover to the soft tissue defect and the created border between the oral and nasal cavity helping in the improvement of the patient's sound of speech. The silicone substitution part provided a non-traumatic distribution of the pressure on tight insertion at areas of the defect and becomes successful in improving patients' speech during monitoring periods with a delay rehabilitation.